1982
DOI: 10.1073/pnas.79.23.7087
|View full text |Cite
|
Sign up to set email alerts
|

Polyamine requirement for efficient translation of amber codons in vivo.

Abstract: Multiplication of several amber mutants of bacteriophage T7 was decreased in two polyamine-deficient mutants of Escherichia coli K-12 carrying amber suppressors, relative to the multiplication ofwild type bacteriophage T7 in the same hosts. In contrast the same T7 amber bacteriophages multiplied well in these strains when supplemented with polyamines. The requirement for polyamines for optimal translation of amber codons in vivo was confirmed by showing that infection of polyamine-depleted E. coli with bacter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

1984
1984
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 29 publications
1
19
0
Order By: Relevance
“…Symbols: 0, growth on minimal medium; 0, growth after addition of arginine; A, growth after addition of ornithine to arginine-treated culture. Polyamines have been shown to influence the fidelity of protein synthesis and to be required in some cases for the action of nonsense suppressor mutations in bacteria (1,11,12,24,25). Our data show that nonsense suppression is qualitatively successful in N. crassa despite severe polyamine starvation in our suppressed mutants.…”
Section: Resultsmentioning
confidence: 99%
“…Symbols: 0, growth on minimal medium; 0, growth after addition of arginine; A, growth after addition of ornithine to arginine-treated culture. Polyamines have been shown to influence the fidelity of protein synthesis and to be required in some cases for the action of nonsense suppressor mutations in bacteria (1,11,12,24,25). Our data show that nonsense suppression is qualitatively successful in N. crassa despite severe polyamine starvation in our suppressed mutants.…”
Section: Resultsmentioning
confidence: 99%
“…Polyamines act in the cells as organic cations at physiological pH. Studies primarily with microorganisms and mammalian cells have yielded supporting evidence for participation of polyamines in protein synthesis (14) and enzyme regulation (6). In higher plants, the gene(s) and/or formation ofa-amylase in isolated barley aleurone layers (8).…”
mentioning
confidence: 99%
“…In related experiments, we later showed that although wild-type bacteriophage T4 grew normally in polyamine-deficient cells, T4 phage containing an amber mutation grew poorly even if the host contained a suppressor tRNA; the latter cells accumulate an amber fragment (71). Therefore, these experiments indicated that the efficiency of nonsense suppression by a suppressor tRNA is very poor in polyamine-deficient cells.…”
Section: Studies On the Physiological Functions Of Polyaminesmentioning
confidence: 87%